The efficacy of Malaysian online smoking cessation website based on Kuantan smokers assessment - Jaafar, Mohamad Helmy; Alias, Normalina; Md Isa, Muhammad Lokman (Malaysian Public Health Physicians' Association, 2021)
Tobacco-related diseases are the leading causes of death worldwide. Tobacco use must be reduced and controlled. Due to its low cost, internet intervention has a high probability of attracting a large number of smokers, however, more research is needed to determine its most effective use. The purpose of this study was to analyze the efficacy of online smoking cessation websites in Malaysia based on assessment by Kuantan smokers. A cross-sectional study using a mix method was conducted among smokers in Kuantan, Pahang. The evaluation is divided into two phases: phase I is the selection of a website by a content expert, and phase II is the review of a selected local website by a local respondent. Random purposive sampling among 35 smokers were recruited in phase 2. There were predetermined criteria in both phase. Website search was conducted thru identified keyword using search engine google. In phase 2, the selected good score website will be assessed by local smokers based on validated checklist. Three websites which were JomQuit.com, Nicorette.com and Quit Smoking Clinic IJN was selected for the review. The website JomQuit.com was identified as comprehensive anti-smoking website in Malaysia. The Malaysian online smoking cessation was believed to be helpful to quit smoking, provide interesting content and information, increase awareness and increase promotion. Regular website assessments must be performed on a regular basis to ensure that the information on the website is applicable to local communities and for content improvement purposes.